The Implementation of Augmented Reality-Based Learning in Computer Network System Courses - Nur Imansyah; Sri Handani W (Universitas Raharja, 2021)
How to deliver teaching materials in lectures is one part that determines students understand the material presented, especially when lecture material is something that requires equipment that supports outdoor activities or requires practicum devices that are not possible to apply to the room for example is practicum about depicting Fresnel Zone and Sometimes monotonous delivery bores students so that they are not interested enough to have difficulty in understanding lecture material. One way that can be done to overcome this is by using visual equipment so that what is conveyed visually makes students interested in the material presented. Submission visually in the room is also a problem when the number of students is large. For that we need equipment that can provide information visually and is easy to use or carry that can stimulate the activities of students to interact. Augmented Reality is a visual model that can provide new experiences in interacting between real objects and virtual objects in the form of three dimensions, using augmented reality packaged as learning material can help students to understand teaching materials in lectures.